Gait Training and Ankle Dorsiflexors in Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators at University of Copenhagen, Denmark, evaluated whether 4 weeks of 30 min daily treadmill training with an incline may facilitate corticospinal transmission and improve control of the ankle joint in 16 children, aged 5-14 years, with cerebral palsy.